Introduction to Health History Interviewing for the Dental Student - Heiko Spallek; Deborah Polk; Kathrin Becker; Jean O'Donnell; Zsuzsa Horvath (Association of American Medical Colleges, 2011)
Abstract This web-based module provides introductory health history interviewing techniques and strategies to students who have no prior interviewing training. It was prepared specifically for dental students. It provides learners with examples relevant to the dental profession and presents techniques, skills, and knowledge needed by a dentist. The module such topics as predictability, controllability, washing one's hands, showing patients where to put their belongings, looking at one's patient while interacting with him or her, phrasing questions to conduct an efficient interview, the different components of a medical interview and their sequence, greeting patients in the waiting room, and bringing patients back to the operating room. One unit introduces the concept of standardized patients (SPs) and explains how to work with them. This tutorial uses e-learning concepts to familiarize students with a "soft" area of their education such as taking a medical history, showing empathy, and handling patients with anxiety as well as with the logistics of the SP encounter (how to give feedback to peers, etc.). Anecdotal evidence gathered from the faculty facilitators indicated that students who used this module in preparation performed significantly better than students who used a textbook. A research paper is in preparation for this educational experiment..